The summer's end - Monroe, Mary Alice (Monroe, Mary Alice. Lowcountry summer trilogy ;, 2015)
"It is summer's end and Sea Breeze, the family's beloved estate on Sullivan's Island, must be sold. It is an emotional time of transition as Mamaw and the three sisters each must face loss and find a new place in the world. Harper, the youngest sister, arrived at Sea Breeze intending to stay only a weekend, but a rift with her wealthy, influential mother left her without direction or a home. During this remarkable summer, free from her mother's tyranny and with the help of her half sisters, Harper discovered her talents and independent spirit. But summer is ending, and the fate of Sea Breeze hinges on Harper's courage to decide the course of her own life. To do so she must release her insecurities and recognize her newfound strengths. She must accept love fully into her life--the love of Mamaw, Carson, and Dora, the love of Sea Breeze and the lowcountry, and most of all, the love of a Wounded Warrior who has claimed her heart" --